Association Between Acute Ischemic Stroke and Raised Serum Gamma Glutamyl Transferase: Association Between Acute Ischemic Stroke and Serum Gamma Glutamyl Transferase - Kanwal, Sibgha; Yousaf, Qudsum; Jamil, Aysha; Arshad, Waqas; Qadir, Momina; Butt, Imad ud Din Yousaf; Tahir, Malik Usman; Rahim, Faisal; Ahmed, Usman; Habib, Umema (Pakistan Journal of Health Sciences, 2024)
The serum gamma-glutamyl transferase level predicts the development of cardiovascular illnesses. Serum gamma-glutamyl transferase levels have been linked to atherosclerosis in several investigations, indicating that gamma-glutamyl transferase may be utilized as an early indicator of atherosclerosis. Objective: To determine the association between acute ischemic stroke and raised serum gamma-glutamyl transferase. Methods: After obtaining ethical approval, in this case-control study, 310 patients fulfilling the selection criteria were included from the Medical Emergency Department of, KEMU/ Affiliated hospital, Lahore from August 2022 to February 2023. Informed consent was obtained. After matching for age (40-80 years) and gender (both male and female), 155 controls enrolled preferably the accompanying healthy attendants of the patients and 155 cases i.e. ischemic stroke patients. Venous blood samples were obtained from cases at the time of presentation in the Emergency Department for serum gamma-glutamyl transferase (GGT). Data was collected in structured proforma. Data scrutiny was done using SPSS version 26.0. Mean and standard deviation were used for quantitative variables and frequency for qualitative data. Data were stratified for effect modifiers, and p≤0.05 was taken as significant. Results: In the current study, the frequency of raised GGT was found more among cases as compared to controls i.e. 74% vs 20%, p<0.00001 and OR calculated was 11.5. Conclusions: It was concluded that a considerable percentage of patients had raised gamma-glutamyl transferase at the time of presentation with acute ischemic stroke. These results emphasize the need to keep an eye on GGT levels in ischemic stroke patients as a possible stroke marker.